Preparation method of composite carbon material, composite carbon material prepared by preparation method and application of composite carbon material
By mixing carbon powder, boron and lead and strontium powder, organic ligands and organic binders, a modified carbon material containing a hydrophobic layer is formed, which solves the sulfateization problem of lead-acid batteries, improves the hydrogen evolution overpotential and extends the cycle life.
Patent Information
- Application Number
- CN202311155418.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-09-08
AI Technical Summary
When the lead-acid battery operates under partially charged state, irreversible lead sulfate accumulates in the negative electrode, resulting in the battery sulfation and failure. The existing technology improves the conductivity by adding carbon materials to the negative electrode, but it brings about hydrogen evolution problem. How to further solve the battery sulfate and increase the hydrogen evolution overpotential of carbon materials is the research focus.
By fully mixing carbon powder, boron and lead and strontium powder, organic ligands and organic binders, a modified carbon material containing a hydrophobic layer is formed, which hinders the contact between the active sites of the carbon material and the hydrogen ions, increases the hydrogen evolution overpotential, and refines the lead sulfate crystal grains by forming metal lead crystal sites to extend the cycle life of the lead carbon battery.
It achieves the effect of improving the hydrogen evolution overpotential of carbon materials and extending the cycle life of lead-carbon batteries, solves the problem of battery sulfateization, and improves the stability and performance of the battery.
Abstract
Description
Technical Field
[0001] The present application relates to a method for preparing a composite carbon material, the composite carbon material prepared therefrom, and applications thereof, and belongs to the field of conductive materials. Background Art
[0002] Lead-acid batteries are widely used in various fields due to their high stability, low production cost, and high safety. However, hybrid vehicles and renewable energy power plants place higher demands on the performance of lead-acid batteries. These applications typically require lead-acid batteries to operate in a partially charged state. This condition leads to the accumulation of large amounts of irreversible lead sulfate at the battery's negative electrode during cycling, causing battery sulfation and failure. To address this issue, lead-carbon batteries were developed. By adding a certain amount of carbon material to the lead-acid battery's negative electrode to enhance its conductivity, the battery's sulfation is mitigated. However, the addition of carbon material introduces the problem of hydrogen evolution. Further addressing this battery sulfation problem and increasing the carbon material's hydrogen evolution overpotential are key research areas in the scientific research community. Summary of the Invention
[0003] The present invention provides a method for preparing a lead-carbon battery negative electrode. Carbon powder, boron and / or lead and / or strontium powder, an organic ligand, and an organic binder are thoroughly mixed. Based on the principle of like dissolves like, the organic ligand can form a sufficient mixture with the binder. Furthermore, the π bonds in the organic ligand allow the boron and / or lead and / or strontium powder to fully bond with the binder, thereby improving the binding properties of the organic binder. The presence of the binder can produce a modified carbon material containing a hydrophobic layer. The hydrophobic layer helps to prevent the active sites of the carbon material from contacting hydrogen ions, thereby increasing the hydrogen evolution overpotential of the carbon material. Furthermore, the boron and / or lead and / or strontium powder can form crystallization sites for metallic lead. The charge and discharge process of a lead-acid battery is a conversion process between metallic lead and lead sulfate. More metallic lead crystallization sites can refine the grain size of the metallic lead in the charging product, indirectly refining the lead sulfate grains in the discharge product, ultimately extending the cycle life of the lead-carbon battery.
[0004] According to one aspect of the present application, a method for preparing a composite carbon material is provided, comprising the following steps:
[0005] A mixed binder containing an organic binder, a metal element, an additive and a solvent is mixed with an activated carbon material, and then dried to obtain the composite carbon material.
[0006] The organic binder is selected from at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR);
[0007] The metal element is selected from at least one of boron, lead, and strontium;
[0008] The additive is selected from at least one of benzothiazole and oxazole;
[0009] The solvent is selected from at least one of N-methylpyrrolidone (NMP), ethanol, acetone, methanol, ethyl acetate, chloroform, benzene, xylene, methyl sulfide, ethyl sulfide, and thiophene.
[0010] The mass ratio of the organic binder to the metal element is 0.01-50g:0.01-10g;
[0011] The mass ratio of the organic binder to the additive is 0.01-50g:0.01-10g;
[0012] The usage ratio of the organic binder to the solvent is 0.01-50 g: 2-200 ml.
[0013] The viscosity range of the mixed adhesive is: (4000-8000) mPa·S.
[0014] The specific surface area of the activated carbon material is 300-3000m 2 / g;
[0015] The mass ratio of the organic binder to the activated carbon material is 0.01-50g:1-1000g.
[0016] The mixing is ball milling.
[0017] The drying temperature is 40-150°C;
[0018] The drying time is 1 to 48 hours.
[0019] According to another aspect of the present application, a composite carbon material prepared by the above-mentioned preparation method is provided.
[0020] According to another aspect of the present application, an electrode is provided, comprising the above-mentioned composite carbon material.
[0021] According to another aspect of the present application, a lead-acid battery is provided, comprising the above-mentioned electrode.
[0022] The beneficial effects of this application include:
[0023] Carbon powder, boron and / or lead and / or strontium powder, an organic ligand, and an organic binder are thoroughly mixed. Based on the principle of like dissolves like, the organic ligand forms a complete mixture with the binder. Furthermore, the π bonds within the organic ligand allow the boron and / or lead and / or strontium powder to fully bond with the binder, enhancing the organic binder's adhesion. The presence of the binder allows for the production of a modified carbon material containing a hydrophobic layer. This hydrophobic layer helps to hinder contact between the carbon material's active sites and hydrogen ions, thereby increasing the carbon material's hydrogen evolution overpotential. Furthermore, the boron and / or lead and / or strontium powder can form crystallization sites for metallic lead. The charge and discharge process of a lead-acid battery is a conversion process between metallic lead and lead sulfate. More metallic lead crystallization sites can refine the grain size of the metallic lead in the charge product, indirectly refining the lead sulfate grains in the discharge product, ultimately extending the cycle life of the lead-carbon battery. DETAILED DESCRIPTION
[0024] The present invention is described in detail below with reference to the embodiments.
[0025] Unless otherwise specified, the raw materials in the examples were purchased from commercial sources and used directly without further treatment; the instruments and equipment used were based on the parameters recommended by the manufacturers.
[0026] In the embodiment, the cycle life of the lead-carbon battery is tested using a Blue Electric charge and discharge instrument and a Newway charge and discharge tester.
[0027] In the examples, the adhesiveness of the adhesive after adding the organic ligand is tested by a rotational viscometer.
[0028] Example 1
[0029] Step 1: Prepare the composite carbon material by the following method:
[0030] First, 2g of polyvinylidene fluoride (PVDF), 0.5g of boron, and 0.5g of benzothiazole were dissolved in 20ml of N-methylpyrrolidone (NMP). The viscosity of the mixture was tested to be 4500mPa·s. Then, 10g of a 1000m2 surface area carbon nanotube was added to the solution. 2 / g of activated carbon material to form a mixture, which was then fully ball-milled and dried in an environment of 80°C for 24 hours.
[0031] Step 2: Prepare lead-carbon battery electrodes and lead-carbon batteries using the following method and perform cycle stability and gas evolution tests:
[0032] 1) Preparation of the negative electrode: (1) Premix 600g of lead powder, 9g of the prepared carbon material, 8.4g of barium sulfate, and 0.3g of polypropylene short fibers with a length of 5mm and a diameter of 0.5-1.5μm in a high-speed blender. Add 84g of deionized water to the premixed powder while stirring, and continue stirring for 10 minutes to obtain a lead paste; (2) Scrape the lead paste onto a metal lead grid with a grid size of 70mm long, 50mm wide, and 2mm thick. Curing and drying are performed to obtain a lead-carbon battery negative electrode. The curing temperature is 40°C, the humidity is 80%, and the curing time is 20 hours; the drying temperature is 80°C, and the drying time is 24 hours.
[0033] 2) Preparation of the positive electrode: The positive electrode of the lead-acid battery is prepared according to the same process steps as the negative electrode preparation steps (1) and (2), except that no carbon material is added to the positive electrode;
[0034] 3) Preparation of lead-carbon battery: three positive plates and two negative plates are placed in parallel with each other in an alternating manner, and a colloidal PE separator for lead-carbon battery is placed between the positive plates and the negative plates. Two negative plates are welded in parallel and three positive plates are welded in parallel, respectively. The total mass of the positive active material of the lead-acid battery (the total mass of the lead paste on the three positive plates after drying) is 60.0 g, and the total mass of the positive active material refers to the total mass of the lead paste contained in the three positive plates welded in parallel. The total mass of the negative active material (the total mass of the lead paste on the two negative plates after drying) is 52.9 g, and the total mass of the negative active material refers to the total mass of the lead paste contained in the two negative plates welded in parallel. The positive and negative electrode grids were conventional lead grids with dimensions of 70 mm long, 50 mm wide, and 2 mm thick. The positive and negative electrodes were placed in a tightly fitted battery box (76 mm long, 40 mm wide, and 100 mm high). 83 g of the sulfuric acid electrolyte prepared above with a mass concentration of 1.275 g / ml was injected into the battery box.
[0035] The battery was subjected to a room temperature life test at 25°C. The test conditions were: discharge at a constant current of 4.2A for 59 seconds, discharge at 18A for 1 second, and charge at a constant current and voltage of 6.3A at 2.3V for 60 seconds. This charge and discharge condition was cycled 3,600 times, followed by a 40-hour rest. The cycle was restarted after 40 hours, with the life test terminated when the battery voltage dropped below 1.2V. The assembled internal hybrid battery was able to run 52,265 cycles in the room temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7,200 cycles), the assembled lead-carbon battery's room temperature cycle life can reach 7.3 times that of traditional lead-acid batteries.
[0036] The battery was subjected to a room-temperature gas evolution test, and the test method was as follows: the battery was fully sealed with laboratory-specific commercial paraffin, and then an air tube was inserted into the exhaust port of the battery. The end of the air tube located inside the battery passed through the rubber plug with a length of 5 mm, and the end of the air tube located outside the working electrode chamber was introduced into the device for testing the gas volume by the water displacement method. The inner and outer surfaces of the rubber plug through which the air tube passed and the various connections between the air tube and the commercial water displacement method gas volume test device were firmly sealed with commercial AB glue, in order to ensure that the gas generated by the battery end was completely introduced into the commercial water displacement method gas volume measurement device, and the gas volume generated by the battery end was collected by the device, and the gas production rate was calculated. During the test, the battery system was placed in a constant temperature environment of 25°C, and a constant voltage of 2.4V was applied to both ends of the battery for 48 hours. It was calculated that the gas production rate of the lead-carbon battery with this formula carbon material was 0.15ml / (wh·h).
[0037] Example 2
[0038] According to the requirements of Example 1, without changing other conditions, the amount of polyvinylidene fluoride (PVDF) added in step 1 was changed to 0.1g, the viscosity of the prepared binder was 4000mPa·s, and the assembled internal hybrid battery could run 30983 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 4.3 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.23ml / (wh·h).
[0039] Example 3
[0040] According to the requirements of Example 1, without changing other conditions, the amount of polyvinylidene fluoride (PVDF) added in step 1 was changed to 20g, the viscosity of the prepared binder was 5000mPa·s, and the assembled internal hybrid battery could run 49709 cycles in the room temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the room temperature cycle life of the internal hybrid lead-carbon battery can reach 6.9 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.17ml / (wh·h).
[0041] Example 4
[0042] According to the requirements of Example 1, without changing other conditions, the activated carbon in step 1 was replaced with a carbon having a specific surface area of 500 m 2 / g of activated carbon, the resulting hybrid battery achieved 39,362 cycles in a room-temperature lifespan test. Compared to a conventional lead-acid battery with the same lead content under the same test conditions (7,200 cycles), the room-temperature cycle life of the hybrid lead-carbon battery is 5.5 times that of a conventional lead-acid battery. The gas production rate of the assembled lead-carbon battery at room temperature is 0.25ml / (wh·h).
[0043] Example 5
[0044] According to the requirements of Example 1, without changing other conditions, the activated carbon in step 1 was replaced with a carbon having a specific surface area of 2500 m 2 / g of activated carbon, the resulting hybrid battery achieved 30,268 cycles in a room-temperature lifespan test. Compared to a conventional lead-acid battery with the same lead content (7,200 cycles) under the same test conditions, the hybrid lead-carbon battery's room-temperature cycle life is 4.2 times that of a conventional lead-acid battery. The gas production rate of the assembled lead-carbon battery at room temperature is 0.21ml / (wh·h).
[0045] Example 6
[0046] According to the requirements of Example 1, without changing other conditions, the amount of boron added in step 1 was changed to 0.1g. The assembled internal hybrid battery can run 49,376 cycles in the room temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7,200 cycles), the room temperature cycle life of the internal hybrid lead-carbon battery can reach 6.9 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.18ml / (wh·h).
[0047] Example 7
[0048] According to the requirements of Example 1, without changing other conditions, the amount of boron added in step 1 was changed to 10g. The assembled internal hybrid battery can run 51,985 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7,200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 7.2 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.14ml / (wh·h).
[0049] Example 8
[0050] According to the requirements of Example 1, without changing other conditions, the boron element in step 1 was replaced with the same mass of lead element. The assembled internal hybrid battery can run 49,874 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7,200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 6.9 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.20ml / (wh·h).
[0051] Example 9
[0052] According to the requirements of Example 1, without changing other conditions, the boron element in step 1 was replaced with the same mass of strontium element. The assembled internal hybrid battery can run 34294 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 4.8 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.22ml / (wh·h).
[0053] Example 10
[0054] According to the requirements of Example 1, without changing other conditions, the benzothiazole in step 1 was replaced with the same mass of oxazole. The viscosity of the prepared binder was 5500mPa·s, and the assembled internal hybrid battery could run 59318 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 8.2 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.20ml / (wh·h).
[0055] Example 11
[0056] According to the requirements of Example 1, without changing other conditions, the amount of benzothiazole added in step 1 was changed to 0.1g, the viscosity of the prepared binder was 4000mPa·s, and the assembled internal hybrid battery could run 49628 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 6.9 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.22ml / (wh·h).
[0057] Example 11
[0058] According to the requirements of Example 1, without changing other conditions, the amount of benzothiazole added in step 1 was changed to 10g, the viscosity of the prepared binder was 7500mPa·s, and the assembled internal hybrid battery could run 57921 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 8.0 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.18ml / (wh·h).
[0059] Comparative Example 1
[0060] Lead-acid battery: According to the requirements of Example 1, without changing other conditions, the second step "1) Preparation of negative electrode: (1) 600g lead powder, 9g prepared carbon material, 8.4g barium sulfate, 0.3g polypropylene short fiber with a length of 5mm and a diameter of 0.5-1.5μm were premixed in a high-speed blender, 84g deionized water was added to the premixed powder while stirring, and the stirring was continued for 10min to obtain lead paste;" was changed to (without adding any carbon material) "1) Preparation of negative electrode: (1) 600g lead powder, 8.4g barium sulfate, 0.3g polypropylene short fiber with a length of 5mm and a diameter of 0.5-1.5μm were premixed in a high-speed blender, 84g deionized water was added to the premixed powder while stirring, and the stirring was continued for 10min to obtain lead paste;" The other steps remained unchanged, and the lead-acid battery was prepared. The assembled internally mixed battery can run 7200 cycles in the room temperature life test. Lead-acid batteries do not have hydrogen evolution issues, so gas generation rate testing is not performed.
[0061] Comparative Example 2
[0062] Lead-carbon battery: According to the requirements of Example 1, other conditions are not changed, and the preparation of composite carbon material is not carried out. The lead-carbon battery with a specific surface area of 1300m 2 / g activated carbon was used as a carbon material additive for lead-carbon batteries. The assembled internal hybrid battery was able to operate for 10,800 cycles in a normal temperature life test. The assembled lead-carbon battery produced a gas production rate of 0.40ml / (wh·h) at room temperature.
[0063] Comparative Example 3
[0064] Following the requirements of Example 1, with no other changes to the other conditions, the amount of polyvinylidene fluoride (PVDF) added in step 1 was changed to 0.01 g. The viscosity of the prepared binder was 5500 mPa·s. The prepared carbon material failed to form an effective hydrophobic layer and failed to increase the hydrogen evolution overpotential of the carbon material. As a result, the assembled internal hybrid battery could only operate for 7200 cycles in the room temperature life test. The assembled lead-carbon battery had a gas production rate of 0.41 ml / (wh·h) at room temperature.
[0065] Comparative Example 4
[0066] Following the requirements of Example 1, with no other changes to the other conditions, the amount of boron added in step 1 was changed to 0 g. The viscosity of the resulting binder was 4500 mPa·s. Although the resulting carbon material formed a hydrophobic layer, it was unable to effectively improve the crystallization of metallic lead and lead sulfate. Furthermore, the carbon material's excessive internal resistance resulted in the assembled internal hybrid battery operating for only 3600 cycles in a room-temperature life test. The assembled lead-carbon battery produced a gas production rate of 0.09 ml / (wh·h) at room temperature.
[0067] Comparative Example 5
[0068] Following the requirements of Example 1, without changing other conditions, the addition of boron in step 1 was replaced with an equal mass of iron. The resulting binder had a viscosity of 4000 mPa·s. The iron was unable to fully bond with the organic binder and form effective lead metal crystallization sites, resulting in the assembled internal hybrid battery operating for only 7200 cycles in a room temperature life test. The assembled lead-carbon battery produced a gas production rate of 0.91 ml / (wh·h) at room temperature.
[0069] Comparative Example 6
[0070] According to the requirements of Example 1, without changing other conditions, the carbon material added in step 1 was replaced with a carbon material of equal mass and having a specific surface area of 10 m 2 / g of carbon material, due to its low specific surface area, cannot provide sufficient crystallization sites for metallic lead, failing to refine the lead sulfate grains. As a result, the assembled internal hybrid battery can only operate for 10,800 cycles in a room temperature life test. The assembled lead-carbon battery has a gas production rate of 0.85ml / (wh·h) at room temperature.
[0071] Comparative Example 7
[0072] Following the requirements of Example 1, without changing other conditions, the benzothiazole added in step 1 was replaced with an equivalent molar amount of oleylamine. The resulting binder had a viscosity of 3000 mPa·s. Oleylamine was unable to form effective complexes with boron, lead, or strontium, thereby failing to enhance the bonding strength of these elements with the carbon material or with the organic binder. Furthermore, it failed to form a large number of metallic lead crystallization sites, and failed to refine the lead sulfate grains. Consequently, the assembled internal hybrid battery only operated for 7200 cycles in a room temperature life test. The assembled lead-carbon battery produced a gas production rate of 0.91 ml / (wh·h) at room temperature.
[0073] The above descriptions are merely a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application discloses the preferred embodiments as above, they are not intended to limit the present application. Any technical personnel familiar with the present profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing a composite carbon material, characterized in that: The following steps are involved: The mixed binder containing an organic binder, a metal element, an additive and a solvent is mixed with an activated carbon material, and then dried to obtain the composite carbon material.
2. The preparation method according to claim 1, characterized in that: The organic binder is selected from at least one of polyvinylidene fluoride, polytetrafluoroethylene, carboxymethyl cellulose and styrene-butadiene rubber; The metal element is selected from at least one of boron, lead and strontium; The additive is selected from at least one of benzothiazole and oxazole; The solvent is selected from at least one of N-methylpyrrolidone, ethanol, acetone, methanol, ethyl acetate, chloroform, benzene, xylene, methyl sulfide, ethyl sulfide, and thiophene.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the organic binder to the metal element is 0.01-50g:0.01-10g; The mass ratio of the organic binder to the additive is 0.01-50g:0.01-10g; The usage ratio of the organic binder to the solvent is 0.01-50 g: 2-200 ml.
4. The preparation method according to claim 1, characterized in that: The specific surface area of the activated carbon material is 300-3000m 2 / g; The mass ratio of the organic binder to the activated carbon material is 0.01-50g:1-1000g.
5. The preparation method according to claim 1, characterized in that: The mixing is ball milling.
6. The preparation method according to claim 1, characterized in that: The drying temperature is 40-150°C; The drying time is 1 to 48 hours.
7. A composite carbon material prepared by the preparation method according to any one of claims 1 to 6.
8. An electrode, characterized in that: Contains the composite carbon material according to claim 7.
9. A lead-acid battery, characterized in that: Containing the electrode according to claim 8.
Citation Information
Patent Citations
Lead-carbon composite material, and preparation method and application thereof
CN103943859A
Preparation method of carbon-based additive used for lead-carbon negative electrode
CN107742696A
Activated carbon composite material and application thereof in lead-carbon battery
CN113948701A
Composite electrode material for lead acid battery and manufacture thereof
JP1990256160A
Bisphenol resin, electrode, lead storage battery and method of producing the same, and resin composition
JP2017160304A